Finite element modeling of Lamb wave propagation in composite stepped joints. (May 2016) - Sherafat, Mohammad H; Quaegebeur, Nicolas; Hubert, Pascal; Lessard, Larry; Masson, Patrice
The objective of this research is to evaluate the integrity of a composite bonded joint by simulating Lamb wave propagation using finite element methods. The structure of interest is composed of two stepped carbon fiber reinforced polymer plates bonded together by an adhesive film. Two different bonding conditions are examined for the joint: undamaged and damaged (with disbond). In the finite element model, an antisymmetric guided wave is excited by imposing an out-of-plane displacement on the surfaces and a spatial Fourier transform is performed before and after the bond line for extraction of reflection and transmission coefficients. For validation, experiments are also conducted using two colocalized rectangular piezoceramics for plane wave generation. A 3D laser Doppler vibrometer is employed for noncontact measurement of the in-plane and out-of-plane velocity. The results confirm the reflections from the steps' edges, and it is found that the level of reflection and transmission of the guided wave mode is different for undamaged and damaged joints. The antisymmetric mode in the pulse-echo configuration seems to be an efficient mode and strategy for disbond detection in composite repairs. The results verify that guided wave propagation is very effective for disbond detection in composite bonded joints and scarf repairs.